Tillage effect on partial budget analysis of cropping intensification under dryland farming in Punjab, Pakistan. Issue 2 (1st February 2016) - Hassan, Asma; Ijaz, Shahzada Sohail; Lal, Rattan; Barker, David; Ansar, Muhammad; Ali, Safdar; Jiang, Shiguo
Abstract : A 2-year research experiment was laid out in a split-plot design with moldboard ploughing (MP, control) and minimum tillage (MT) as main plots and crop sequences as sub-plots. Summer-winter cropping sequences were fallow-wheat ( Triticum aestivum L.) (FW, control), mungbean ( Vigna radiata L.) -wheat (MW), sorghum ( Sorghum bicolor L.)-wheat (SW), green manure-wheat (GW) and mungbean-chickpea (MC) ( Cicer arietinum L.). During 2010–2011, in summer, mungbean crop produced the highest above ground biomass in mungbean-chickpea sequence under MP tillage (4.24 Mg ha – 1 mungbean) and in mungbean-wheat sequence under MT tillage (4.11 Mg ha – 1 mungbean). In winter, chickpea gave the highest biomass in mungbean-chickpea sequence under both tillage systems. During 2011–2012, mungbean produced the highest above ground biomass in mungbean-wheat sequence under MT tillage (4.43 Mg ha – 1 mungbean) and in both the mungbean-chickpea and mungbean-wheat sequences under MP tillage (4.24 and 4.17 Mg ha – 1 mungbean, respectively). In winter, fallow-wheat sequence gave the highest biomass in both tillage systems. The differences in grain yields were statistically non-significant in both the years. The gross marginal benefit ranged between −190 and 548$ ha – 1 in the first year and −165 and 1124$ ha – 1 in the second year. The net benefit values were the highest in mung-chickpea sequence under both tillage systems (1008 and 596$ ha – 1 under MP and MT, respectively), which gave cost–benefit ratios of 5.45 and 3.68, respectively. Use of legume-based cropping sequences is a sustainable and cost-effective practice in drylands of northern Punjab, Pakistan.